Meta-Mortgaging: Islamic Law Review on Marhūn Issues - Muhammadi, Fauzan; Putranti, Deslaely; Praja, Chrisna Bagus Edhita; Yudha, Alda Kartika (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2000)
To this date, technology has seen massive development and, it influences the economic field. The emergence of the metaverse has become an inevitable part of this progress. It serves as a digital world, wherein everyone is able carry out a vast array of activities, including economic transactions. The emergence of digital assets, that has encouraged serious discussion, is inseparable from Islamic law. One of these digital assets is the Non-Fungible Token (NFT). This digital asset is the focus of this study, specifically on for its posibility to become material guarantees. This article employs a qualitative study and presented descriptively through the perspective of Islamic law. The result of this study is that the pledged-object (marhūn) has certain primary conditions for it to be functional, namely: it is a property, it has value, it can be traded, its asset value is clearly known, and it is actually owned by the guarantor (rāhin). The concept of marhūn as a valuable object ultimately answers that NFT is included in the marhūn category. However, since NFTs do not stand alone if the transaction currency used in the metaverse is cryptocurrencies, al-rahn transactions using NFTs become less favourable considering Cyrptocurrency is deemed to be haram.